Implementación de experimentos caseros como recurso didáctico de enseñanza aprendizaje de química con estudiantes de 2do de bachillerato de la Unidad Educativa “Carlota Jaramillo”. - Uyaguari Zhagñay, Silvia Paola (2025)
Currently, learning Chemistry represents a significant challenge for educators, leading to the recommendation to use engaging teaching strategies such as home experiments. This research focuses on the question: How does the implementation of home experiments influence the learning of chemistry among second-year high school students at the Carlota Jaramillo Educational Unit? The main objective was to determine the impact of implementing home experiments as a teaching resource for teaching and learning chemistry. The methodology adopted a quantitative approach with a pre-experimental and systematic design. The research was documentary-based, and a teaching guide for the use of home experiments in Chemistry was designed. The research level was descriptive, explanatory, and laboratory-based. Data collection involved a 10-question strategic survey to analyze the level of acceptance of the methodological guide, complemented by written assessments and test-retests to measure learning achievement in the subject. The study population consisted of students from the "Carlota Jaramillo" Educational Unit, from which a sample of 25 students was selected through probability-intentional sampling. It was concluded that the implementation of home experiments as a teaching resource in chemistry teaching at the "Carlota Jaramillo" Educational Unit has demonstrated a positive impact on the learning process. Students have improved their understanding of chemical concepts by linking theory with practice. Since these experiments were accessible and practical, they not only facilitated their understanding but also increased interest and curiosity about the subject.